2018
DOI: 10.1016/j.talanta.2018.01.049
|View full text |Cite
|
Sign up to set email alerts
|

A combined Surface Enhanced Raman Spectroscopy (SERS)/UV–vis approach for the investigation of dye content in commercial felt tip pens inks

Abstract: A B S T R A C TThe development of protocols for the protection of the large patrimony of works of art created by felt tip pen media since the 1950's requires detailed knowledge of the main dyes constituting commercial ink mixtures. In this work Surface Enhanced Raman Scattering (SERS) and UV-vis spectroscopy were used for the first time for the systematic identification of dye composition in commercial felt tip pens. A large selection of pens comprising six colors of five different brands was analyzed. Intense… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 31 publications
0
14
0
Order By: Relevance
“…The summary of all analyzed felt‐tip pens and the dye composition attribution is presented in Table . Interestingly, some of the pens analyzed in this work were also previously analyzed by a combined bench‐size SERS/UV vis spectroscopic approach . The direct comparison between spectra recorded at 514‐nm illumination with benchtop instrumentation and spectra recorded in this work at 785‐nm illumination with handheld instrumentation showed that sharper peaks with better signal‐to‐noise ratios were obtained with benchtop instrumentation.…”
Section: Resultsmentioning
confidence: 70%
See 1 more Smart Citation
“…The summary of all analyzed felt‐tip pens and the dye composition attribution is presented in Table . Interestingly, some of the pens analyzed in this work were also previously analyzed by a combined bench‐size SERS/UV vis spectroscopic approach . The direct comparison between spectra recorded at 514‐nm illumination with benchtop instrumentation and spectra recorded in this work at 785‐nm illumination with handheld instrumentation showed that sharper peaks with better signal‐to‐noise ratios were obtained with benchtop instrumentation.…”
Section: Resultsmentioning
confidence: 70%
“…SERS was also used by our group and others for the identification of dye content in ballpoint pens . Recently, SERS was also used in combination with other analytical techniques for the identification of dyes in commercial felt‐tip pens and used to identify colorants in colored inks used by artists such as Lucio Fontana and Federico Fellini . As an increasing number of modern artworks are already entering a state of high degradation, the inherent noninvasiveness, high sensitivity, and efficient quenching of interfering fluorescence signals could make SERS the analytical technique of choice to support the development of long‐term conservation methods for modern artworks.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, our group has successfully applied Raman and SERS, in combination with bench and handheld instrumentation, for the identification of the major dye constituents of felt tip pens . The application of SERS allowed circumventing fluorescence interference and provided high intensity spectral profiles of fluorescent dyes under visible wavelength illumination …”
Section: Introductionmentioning
confidence: 99%
“…[27,28] The application of SERS allowed circumventing fluorescence interference and provided high intensity spectral profiles of fluorescent dyes under visible wavelength illumination. [29] In this paper, we report on the application of Raman and SERS spectroscopies to the identification of dye mixtures in colored BIC ballpoint pens. Ten BIC ballpoint pens with different hues of green, purple, pink, and red were analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…A growing number of research publications on the detection of illegal additives [12], pesticide residues [13,14,15,16] and veterinary drugs in foodstuff are available [17,18]. There are some reports on the use of SERS for the detection of tartrazine [19,20,21] but the number of publications on the determination of tartrazine in foodstuff on the basis of the SERS method is relatively low. In 2016, SERS coupled with Au nanodumbbells was used to analyze tartrazine in drinks [22].…”
Section: Introductionmentioning
confidence: 99%